2008
DOI: 10.1111/j.1526-100x.2008.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Locally for Urban Forest Restoration: A Simple Method Links Exotic Species Invasion to Local Landscape Structure

Abstract: Restoring urban forests often involves eradicating exotic species and diligently guarding against future invasions. Understanding how landscape structure contributes to the distribution of exotic species may inform these management efforts. To date, the distribution of exotic species in forested patches has been correlated with the type of development surrounding the patch, with those surrounded by agricultural or urban development often more highly invaded. Yet, previous studies have categorized land use type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Many of these cultivars have been repeatedly introduced in cities or villages throughout the world, facilitating a Bspillover effect^and spread beyond their planting zones (Reichard and White 2001). As is often the case where managed and natural landscapes abut, several of the landscape plants have become naturalized within the urban riparian forest (Richardson et al 2000;Vidra and Shear 2008;Blitzer et al 2012;Litteral and Wu 2012). Genetic studies would be useful to confirm that the Phoenix urban plantings were indeed the source of the naturalized riparian populations along the Salt River (Vardien et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Many of these cultivars have been repeatedly introduced in cities or villages throughout the world, facilitating a Bspillover effect^and spread beyond their planting zones (Reichard and White 2001). As is often the case where managed and natural landscapes abut, several of the landscape plants have become naturalized within the urban riparian forest (Richardson et al 2000;Vidra and Shear 2008;Blitzer et al 2012;Litteral and Wu 2012). Genetic studies would be useful to confirm that the Phoenix urban plantings were indeed the source of the naturalized riparian populations along the Salt River (Vardien et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Assisted reclamation of ex-mining areas recover faster than nonassisted ones, both in the rate of topsoil accumulation and biomass increase of plants (Pietrzykowski 2008). In the beginning of revegetation, plant's growth must be assisted from cosmopolitan alien species that are able to survive in unfavorable environmental conditions, in order to create a favorable ecosystem (Herrick et al 2006;Vidra and Shear 2008). The presence of recolonizing species which are more adaptive and mostly invasive might disrupt the growth of local plant species in the reclamation area.…”
Section: Discussionmentioning
confidence: 99%
“…However, while many studies of sites along urban-to-rural gradients have documented higher amounts of invasion in the urban than in the rural sites in both existing vegetation (Moffatt et al 2004;Borgmann and Rodewald 2005;Loewenstein and Loewenstein 2005) and in seed rain and seed banks (Kostel-Hughes and Young 1998;Honu and Gibson 2008;Lin and Cao 2009), comparisons of sites within developed regions have demonstrated that there is great variability in the degree of invasion among such sites, often correlated with differences in the surrounding types of urban land use (Ehrenfeld 2008;Oneal and Rotenberry 2008;Vidra and Shear 2008). Although these studies document the range of invasion found in urban regions, the mechanisms generating differences in invasion among urban land uses remain unknown.…”
Section: Introductionmentioning
confidence: 98%